Spectral-Efficient Reconstructed LACO-OFDM Transmission for Dimming Compatible Visible Light Communications - Baolong Li; Wei Xu; Simeng Feng; Zhengquan Li (IEEE Photonics Journal)
Dimming control is critical in practical visible light communication (VLC) systems to satisfy illumination demand. Upon exploiting multiple layers of asymmetrically clipped optical orthogonal frequency division multiplexing (ACO-OFDM) signals for simultaneous transmission, layered ACO-OFDM (LACO-OFDM) constitutes a promising spectral-efficient modulation technique for VLC. However, dimming by integrating the industry-preferred pulsewidth modulation (PWM) to the LACO-OFDM scheme induces severe clipping noise due to the nonlinearity of LEDs. In this paper, we conceive a reconstructed LACO-OFDM (RLACO-OFDM) scheme incorporating the PWM technique for VLC to accommodate the dimming demands for indoor illumination, while maintaining a spectral-efficient communication link. Moreover, superior to its counterparts, the transmitted symbols in the RLACO-OFDM based VLC system can be readily recovered by a standard LACO-OFDM receiver while no additional detection of the PWM signal is required, which reduces the receiver complexity. Numerical results demonstrate that the proposed RLACO-OFDM is capable of realizing high spectral efficiency over a broad dimming range.